A Study of Corrosion-Erosion Behavior of Low and High Carbon Steels in Acid and Sand Environments Using Taguchi's Experimental Design - Rattanakool, Tanarat; sukkrajang, kantamon; Kaewdee, Chatchai; Pansrinual, Weeraphol; Sudsomboon, Weerayute (Academic Journal of Industrial Technology Innovation, 2024)
This research aims to investigate and compare the corrosion-erosion behavior of low carbon steel (AISI 1018) and high carbon steel (AISI 1060) under different environmental conditions. A Taguchi experimental design was employed to efficiently evaluate the effects of rotational speed (1,800, 3,600, and 5,400 RPM) and three environmental conditions: distilled water with sand, sulfuric acid solution at pH 4, and sulfuric acid solution at pH 4 with sand on weight loss. An L9 orthogonal array and a rotating cylinder electrode (RCE) setup were utilized for the experiments. Both steel types exhibited good corrosion-erosion resistance, particularly in the sulfuric acid solution at pH 4 without sand. Signal-to-noise ratio (S/N) analysis indicated slightly better performance for high carbon steel (S/N = 53.9) compared to low carbon steel (S/N = 52.4). These findings can be applied to select suitable materials for applications demanding resistance to diverse environments, especially those with high acidity. The application of Taguchi methodology facilitated efficient experimental planning and analysis, enabling informed material selection.